2013
DOI: 10.1002/cncr.28374
|View full text |Cite
|
Sign up to set email alerts
|

Survival and toxicity in patients with disseminated germ cell cancer aged 40 years and older

Abstract: BACKGROUND: Germ-cell cancer (GCC) patients aged 40 years have a two-fold higher GCC-specific mortality. It has been hypothesized that reduced treatment intensity combined with increased treatment related toxicity could be the explanation. The objective was to analyze chemotherapy intensity, treatment related toxicity and survival in patients aged 40 years treated with standard chemotherapy for GCC compared with a younger control group that received similar treatment during the same period. METHODS: From 1984 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The recommended dose and administration schedule in the National Comprehensive Cancer Network (NCCN) guideline is bleomycin 30 units per week; etoposide 100 mg/m 2 /day daily for days 1-5; and cisplatin 20 mg/m 2 /day daily for days 1-5 for 3-4 cycles [12]. However, the BEP regimen is sometimes administered with a reduced dose of bleomycin and/or etoposide because of the potential for serious adverse reactions such as severe bone marrow suppression, pulmonary fibrosis or secondary leukaemia [13][14][15][16][17]. Therefore, the present study investigated whether the use of BEP, especially standard-dose BEP, is associated with OS in patients with YST, in addition to other prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…The recommended dose and administration schedule in the National Comprehensive Cancer Network (NCCN) guideline is bleomycin 30 units per week; etoposide 100 mg/m 2 /day daily for days 1-5; and cisplatin 20 mg/m 2 /day daily for days 1-5 for 3-4 cycles [12]. However, the BEP regimen is sometimes administered with a reduced dose of bleomycin and/or etoposide because of the potential for serious adverse reactions such as severe bone marrow suppression, pulmonary fibrosis or secondary leukaemia [13][14][15][16][17]. Therefore, the present study investigated whether the use of BEP, especially standard-dose BEP, is associated with OS in patients with YST, in addition to other prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…4). In addition, TGCT-specific mortality is reported to increase with increasing age at diagnosis (21,22). Seminoma patients might be at a particular risk of treatment-associated late toxicity due to increased median age at diagnosis, explaining the more rapid decline in RS (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that age greater than 40 years gave a 2.3-fold increased risk of BPT [12]. A recent Danish study including measurements of lung function before each cycle and during follow-up reported that most men aged Z40 years tolerated bleomycin if the lung function was monitored carefully, with discontinuation of bleomycin if DLCO decreased 425% during treatment [32]. No patients aged Z40 years experienced a fatal BPT.…”
Section: Agementioning
confidence: 97%